Beneficial role of Stevia rebaudiana dry extract on the blood glucose reduction in the chronic diabetes mellitus - Sari, Flori R; Hendarto, Hari; Alfan, Djamal; Anwar, Saiful; Adhiyanto, Chris; Wulandari, Rizkiani Juleshodia (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction: Prolonged hyperglycemia may lead to several detrimental microvascular or macrovascular complications in the chronic diabetes mellitus. Thus, achieving normal glycemic condition remains the most important strategy in the diabetes mellitus. Stevia rebaudiana plays an important role on the blood glucose reduction, however, its role in the chronic diabetes mellitus has not been fully elucidated yet. Method: Stevia rebaudiana dry extract (400 mg/kg BW) were given daily by oral gavage for 84 days in rat with diabetes. The measurement of blood glucose concentration were done monthly during the study. Urine output was analyzed on the day 1 and 84. Additionally, lipid profile were measured on the day 84. Results: Compared to the normal rat, significant hyperglycemia were observed in the diabetic rat. Blood glucose concentration tends to decrease in the rat received Stevia rebaudiana extract (St), however, significant difference was achieved on the day 84 of the study confronted to the diabetic rats. Moreover, lower concentration of plasma cholesterol concentration and urine output reduction was significantly observed in the St rat compared to the D rat on the day 84. Discussion: Daily intake of Stevia rebaudiana extract on its therapeutic doses may play beneficial role in the chronic diabetes mellitus by gradually reduced blood glucose concentration, urine output and plasma cholesterol concentration. However, further cellular analysis were required to explicate the exact mechanism. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 22-26